FRAÇÃO CASCALHO DO SOLO SALTINHO DE PIRACICABA, SP - Campos, Douglas Alberto Ferraz de; Perecin, Dilermando; Borduchi, Henrique (REVISTA DE AGRICULTURA, 2016)
FRAÇÃO CASCALHO DO SOLO SALTINHO DE PIRACICABA, SP